Financial Statements: Form, Analysis ad Interpretation (Book). - Gregory, Robert H. (The Accounting Review, 1953)
Reviews the book "Financial Statements: Form, Analysis and Interpretation," edited by Ralph Dale Kennedy and Stewart Yarwood McMullen.